Grandparents as Guards: A Game Theoretic Analysis of Inheritance and Post Marital Residence in a World of Uncertain Paternity - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2012)
I unify the following (1) men face paternal uncertainty while women do not face maternal uncertainty, (2) putative fathers and paternal kin care about true paternity, (3) paternity confidence is systematically lower in matrilocal cultures than in patrilocal ones, (4) inheritance tends to be patrilineal in high paternity confidence cultures and matrilineal in low confidence ones, and (5) most societies with patrilineal inheritance were patrilocal while most societies with matrilineal inheritance were matrilocal. I model the co-evolution of inheritance patterns and post-marital residence patterns - and their relationship with paternity uncertainty. Using a game theoretic model, I examine how a "high paternity confidence" patrilocal-patrilineal equilibrium and a "low paternity confidence" matrilineal-matrilocal equilibrium could emerge. The endogenous choice of the old to monitor the sexual behavior of the young women who reside with them, thereby affecting the paternity confidence of the young women's husbands and hence their productive incentives, is crucial.